Hadith About Major Sins - Endang Nur Fitriani; Uus Husni Hoer; Fajar Solihin; Neng Zulfa Alawiyah; Rizqi Nazwa Ramdhani (Penerbit Hellow Pustaka, 2025)
This writing discusses major sins, associating partners with Allah, and seven types of major sins from the perspective of quran and hadith. The results of this research indicate that major sins are all prohibitions that come from Allah and His Messenger. There are many major sins, including: shirk (associating partners with Allah), disobedience to parents, unlawfully killing a soul, bearing false witness, practicing magic, accusing believing women of adultery, killing a child out of fear of poverty, consuming the property of orphans, engaging in usury, fleeing from battle, and committing adultery with a neighbor's wife, among others. Additionally, disobedience to parents is also considered a major sin and one that leads to destruction. It is essential for us to be obedient to both parents in accordance with Islamic law. However, among all the sins categorized as major, shirk occupies the highest position (the greatest) compared to other major sins. Other major sins not mentioned in hadith, but criteria for major sins in other hadiths, include disobedience to parents, killing a child due to fear of increasing poverty, false testimony, betrayal in matters of spoils, adultery, theft, consuming alcohol, separating oneself from the community, spreading slander, violating oaths of allegiance, and failing to cleanse oneself after urination.